The Khar Tsagaan Us Inscription - Tsend, Battulga; Batdelger, Amgalanbat (Studia Archaeologica, 2024)
The Khar Tsagaan Us Inscription was originally found in 1981 by Academician D. Tseveendorj. It is situated at the boundary of the Baruunturuun and Züünkhangai soums of the Uvs province. Based on the manuscripts and photographs of the that time, there was virtually little opportunity to decipher the inscription. Therefore, the researchers went to the Khar Tsagaan Us more than once to look at the inscription but returned without finding them. That’s the reason no one has read or figured out the inscription. The inscription, which consists of five letters, is read, and translated as `~ äsäη ärli ~ There is a peaceful place`. Alternatively, the translation means “a land of peacefulness, a land of serenity.” Хар цагаан усны бичээс Товчлол. Увс аймгийн Баруунтуруун, Зүүнхангай сумын зааг нутагт орших Хар цагаан усны бичээсийг 1981 онд анх академич Д.Цэвээндорж гуай илрүүлжээ. Бичээсийг тухайн үеийн гар хуулбар, гэрэл зурагт тулгуурлан унших боломж тун бага байсан байна. Бид тус өгүүлэлд Хар цагаан усны Мөртийн цахир хаданд байх таван үсэг тэмдэгтээс бүтэх уг бичээсийг тайлж уншсан судалгааны үр дүнгээс танилцуулж байна. Уг бичээс нь ~ äsäη ärli ~ Эсэн газартай` буюу Амар амгалан газар нутаг бүхий, Эсэн энхийн газар нутагтай гэсэн утгатай юм. Түлхүүр үг. Увс аймаг, Хар цагаан ус, Мөртийн цахир хад, руни бичиг